2021
DOI: 10.1111/agec.12625
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of COVID‐19 induced income and rice price shocks on household welfare in Papua New Guinea: Household model estimates

Abstract: Concerns over the potential effects of the COVID‐19 pandemic have led to trade restrictions by major rice exporters, contributing to an average 25% increase in Thai and Vietnamese rice export prices between December 2019 and March–September 2020. This article assesses the consequences of these rice price increases in Papua New Guinea (PNG), where 99% of rice is imported. Utilizing data from a PNG 2018 rural household survey along with earlier national household survey data, we examine rice consumption patterns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…In sum, COVID-19 affected both supply and demand of food markets, resulting in higher food prices, leading to food insecurity and poverty in many developing and emerging countries. As mentioned above, various studies have investigated economy-wide impacts of COVID-19 induced turmoil [ 45 , 46 ], effects on labor markets [ 23 , 33 , 47 , 48 ], household income and food security [ 14 , 26 , 28 , 36 , 38 , 49 52 ], and trade flows [ 41 , 53 ]. However, the literature on price effects of the COVID-19 pandemic is minimal.…”
Section: Introductionmentioning
confidence: 99%
“…In sum, COVID-19 affected both supply and demand of food markets, resulting in higher food prices, leading to food insecurity and poverty in many developing and emerging countries. As mentioned above, various studies have investigated economy-wide impacts of COVID-19 induced turmoil [ 45 , 46 ], effects on labor markets [ 23 , 33 , 47 , 48 ], household income and food security [ 14 , 26 , 28 , 36 , 38 , 49 52 ], and trade flows [ 41 , 53 ]. However, the literature on price effects of the COVID-19 pandemic is minimal.…”
Section: Introductionmentioning
confidence: 99%
“…A devaluation of the Kina in 1994 and again in 1998 saw the cost of the predominately imported rice increase significantly, making local fresh produce relatively more affordable (Mellor, 2010;Sharp, 2021). Consequently, research from 2009/2010 found urban households were consuming 59.2 kg per person annually, down from its peak in 1996 (Schmidt et al, 2021). Covid-19 related shocks in 2020/2021 have seen the price of rice increased by 30%, and urban incomes reduced by 15%; thus household rice consumption has reduced by almost 20% (Schmidt et al, 2021).…”
Section: Urban Diets In Port Moresbymentioning
confidence: 99%
“…Consequently, research from 2009/2010 found urban households were consuming 59.2 kg per person annually, down from its peak in 1996 (Schmidt et al, 2021). Covid-19 related shocks in 2020/2021 have seen the price of rice increased by 30%, and urban incomes reduced by 15%; thus household rice consumption has reduced by almost 20% (Schmidt et al, 2021). Prior to Covid-19 related shocks, authors had proposed that the growth in rice consumption in Port Moresby had plateaued (Bourke and Harwood, 2009;Gibson, 2019).…”
Section: Urban Diets In Port Moresbymentioning
confidence: 99%
See 1 more Smart Citation
“…We disaggregate the BACI 6-digit trade database by food type to evaluate changes in agri-food trade, by average volumes and values over two five-year periods (2001–05 and 2014–18). 2 Overall, agri-food imports comprised 16% of total imports between 2014 and 2018 and remain crucial to supporting food security and dietary diversity within PNG [ 42 ]. Rice and wheat (flour) combined comprised 24% of total agri-food imports between 2014 and 2018, with rice imports making up the largest share (16%) of overall agri-food import values (Table 1 ).…”
Section: Overview Of Png Food Importsmentioning
confidence: 99%